O2 activation in cytochrome oxidase and in other heme proteins - Babcock, Gerald T.; Zhang, Yong; Varotsis, Constantinos (My University, 1992)
In applying room-temperature, time-resolved optical and resonance-Raman spectroscopies to the cytochrome oxidase/dioxygen reaction, we have been fortunate in being able to detect intermediates in this process both before and after the O-O bond scission reaction occurs (e.g., Refs. 1-9). This behavior contrasts markedly with the situation in the cytochromes P-450 (P450), for example, where the structure of key intermediates, subsequent to the initial oxy complex [10], in the bond cleavage and substrate hydroxylating reactions have been inferred from model studies, chemical reasoning, and genetic modification, but have not been detected directly
Keywords: Cytochrome oxidase; Hemoproteins; Oxygen; Metabolism; Enzymes